Probleme der wirtschaftlichen Integration des Ost-Mitteleuropas (1992-1999) [Problems of economic integration in Central and Eastern Europe (1992-1999)] - Szczepaniak, Marian (Studia Historiae Oeconomicae, 2001)
In 1949-1990, the Central and Eastern European countries and the Soviet Union integrated into the Council for Mutual Economic Assistance. In this organization, relations between the Soviet economy and the economies of individual partners were predominant. CMEA collapsed after the turn of 1989. Its actual collapse occurred in 1991, after the ruble settlements were replaced by dollar settlements. As a result, trade between the former partners fell catastrophically, because everyone suffered from the lack of convertible currencies, and these could only be obtained from surplus trade with the West or from Western loans.